Design and development of a stimuli-responsive oral tablet system for the treatment of ulcerative colitis - Bawa, Priya (My University, 2011)
Ulcerative colitis (UC), notorious for its unpredictable attacks of inflammation of the large intestine, is estimated to affect as many as 1.4 million people in the USA and 2.2 million people in Europe with 15000-30000 new cases being diagnosed annually worldwide. The chronic inflammatory process is limited to various regions of the colonic mucosa and is postulated to occur due to a dysregulated mucosal response in the intestinal wall, facilitated by defects in the protective barrier function of the intestinal epithelium and mucosal immune system. Due to the range and extent of disease manifestations the goals of UC therapy are broad and non-specific. The focus of therapy is thus primarily placed on the treatment of active disease by ameliorating the signs and symptoms characteristic of the disease state with concurrent adjunctive and anti-inflammatory therapy. Thus, ideally a delivery system should facilitate a reduction in the pill burden, daily dosing requirements and allow for concurrent adjunctive and anti-inflammatory therapy with a single delivery system administration. Therefore, essentially the purpose of this work was to develop a novel stimuliresponsive oral tablet system (SROT) that provided targeted drug delivery of 5-ASA to the colon and loperamide HCl to the small intestine with a single delivery system. For this purpose, the employment of polymers that are termed ‘stimuli-responsive’ or ‘smart’ were established to be the most attractive approach for ‘activating’ drug release at the desired site in response to the pre-determined reliable stimulus. Thus, advantage is taken of the over 400 distinct species of anaerobic bacteria and their corresponding enzymatic activities in the colon. Investigations performed according to a Box-Behnken experimental design exposed an optimum enzyme-responsive colon-targeted tablet that effectively inhibited premature 5-ASA release in conditions simulating the upper gastrointestinal tract, whilst enabling an immediate initiation of drug release on exposure to colonic enzymes. The enzyme-responsiveness of the tablet was a direct result of the employment of only naturally-derived polysaccharides that were susceptible to colonic degradation. Furthermore, and more importantly, the prevention of premature drug release was achieved by the enzyme-responsive hydrophobic coating consisting of pectin and an aqueous ethycellulose dispersion that was applied to tablets until a ±10% total weight gain was achieved. In addition the in situ crosslinking between pectin and BaCl2 in the tablet matrix as well as the crosslinked 5-ASA-loaded granules resulted in a zero-order drug release throughout the 18 hour period in the simulated colonic environment containing enzymes. The development of the outer pepsin-responsive small intestinally-targeted coating was also conducted according to the Box-Behnken experimental design. Extensive investigations revealed an optimized pepsin-responsive coating after conducting the relevant studies on the 15 statisticallyderived formulations. Essentially, the tablets coated with the 40%w/v gelatine solutions resulted in the greatest increase in weight and shell thickness of the formulations however these were the least responsive to pepsin. The optimum pepsin-responsiveness was achieved from a gelatine coating of 14.379%w/v which was crosslinked for 6 hours in a glutaraldehyde-lactose dry mixture. Furthermore, the novel crosslinking method ensured that no entrapped loperamide HCl was prematurely lost during the crosslinking process. In addition, the optimum formulation also achieved 100% drug release in the small intestine-at its site of therapeutic action. In vivo investigations of the SROT in the large white pig model explicated the colon-targeting ability of the 5-ASA-loaded tablet as well as the benefits of the SROT compared to the conventional commercially available system, Asacol® (Aventis Pharma (Pty) Ltd.,Midrand, Johannesburg, South Africa). The success of the loperamide-loaded coating was evident from the minimal presence of loperamide HCl in plasma in the first 2 hours post-dosing compared to its commercially available counterpart Imodium® (Janssen Pharmaceutica (Pty) Ltd., Woodmead, Johannesburg, South Africa). Investigations into an alternate colon-targeted drug delivery system revealed 3 novel composite polyacrylamide-polysaccharide hydrolyzed electrolytic matrices consisting of either pectin, chitosan or a combination of both, complexed with hydrolyzed polyacrylamide. Each matrix presented with varying surface area and porositometric properties which influenced their drug release behaviour. These formulations hold potential for numerous controlled drug delivery applications and are not exclusively limited to colon-targeting.
M.Pharm., Department of Pharmacy and Pharmacology, Faculty of Health Sciences, University of the Witwatersrand, 2011.
Keywords: tablet; treatment; ulcerative colitis